Adaptation of foreign students in the Eurasian Economic Union countries as a factor of demographic security - V. Yu. Ledeneva (Вестник университета, 2025)
The article is devoted to the study of adaptation programmes for foreign students in the countries of the Eurasian Economic Union (hereinafter referred to as EAEU) in the context of demographic security. The purpose of the study is a comprehensive comparative analysis of programmes for the adaptation of foreign students in the EAEU countries, in order to identify their features and differences as well as to analyse the potential consequences of these programmes for demographic security. The article discusses approaches to the integration of foreign students and creates a theoretical basis for further studies of the dynamics of educational migration and its impact on the demographic indicators of the EAEU countries. Previously, the problem was not the subject of scientific research, despite the fact that a significant number of scientific articles are devoted to the EAEU issues, but most of them are focused on the economic aspects of integration. Less attention has been paid to migration issues in general and the integration of the educational space in particular. A new concept has been introduced into scientific circulation – demographic integration, which is considered along with demographic security and means a set of processes and mechanisms that contribute to the harmonious and sustainable inclusion of migrants in the socio-economic structure of the EAEU countries. The article uses the methods of comparative analysis, content analysis of adaptation programmes to assess their experience of integration in the country of reception. Recommendations have been developed to improve adaptation programmes for foreign students, which in the future can contribute to strengthening demographic security in the EAEU countries.